The impact of innovations on performance of Singapore logistics firms (aviation sector) - Ng, Wei Lin (2018)
As Singapore is a leading logistics hub in the world, Singapore faces the pressure to continue to innovate and to keep its position. With globalization, companies enter a larger playing field with competitors from all over the world. Furthermore, customers’ expectations have been rapidly increasing over the years and due to them gaining bargaining power, companies face pressure to meet these expectations and retain their customers. Singapore government has been encouraging innovations by providing fund to mitigate the risks. However, due to the government proving fund for the Small, Medium Enterprises (SMEs), traditional companies face the threat of irrational pricing. Air freight may be low in volume but it takes up 35% of international transport in terms of volume. Over the years, the volume transported by air has also been on the rise. Innovations have been found to help the companies save time, save cost, save space and improve reputation. Through this, other factors such as improve in revenue and employee satisfaction can be interpreted. Saving time occurs when companies invest in one machine to handle the work of two machines such that the products do not need to be transferred to another machine. Time can also be saved by reducing failure rate of manufacturing products and by automated scanning of parcels. Costs can be saved by decreasing storage space required as product can be manufactured quickly and by using cheaper yet stronger materials. Costs that are saved can be used by the company for investment purposes as well. By complying with regulations and by promoting green initiatives will boost the company’s reputation and attract more customers. The future of logistics is still broad and more automation will enter the market, especially robots and drones. Many countries are testing out these new technologies and they are expected to enter the market in the short run.